Myocardial Dysfunction in Elderly Patients Admitted with Non-Cardiac Diagnosis in Intensive Care Unit - Dr. Yeshavanth G.; Dr. Edwin Joy; Dr. Aravind Bhagavath (International Journal of Medical Research and Review, 2021)
Background and Objectives: The diagnosis of acute coronary syndromes can be challenging in patients admitted with the non-cardiac disease to the Intensive Care Unit (ICU). The study aimed to determine the clinical profile of critically ill elderly patients developing myocardial injury who were admitted to ICU for non-cardiac diagnosis.Materials and Methods: The retrospective study subjects are 130 patients admitted to the medical ICU. Within 24 hours of admission to ICU a detailed history, a 12 lead ECG, CK-MB, Cardiac troponin T was done and as required based on ECG findings and development of clinical symptoms.Results: Our study showed that 35 out of 130 patients developed acute myocardial injury. 13 out of 35 patients who had myocardial injury had a fatal outcome. The prevalence of hypertension, diabetes mellitus, history of CVA, history of IHD and COPD reached statistical significance (p<0.001) between the two groups of patients who developed myocardial injury and who did not develop a myocardial injury. In patients with multiple comorbidities, the presence of factors like hypoxia, hypotension and the use of vasopressors increases the risk of mortality.Conclusion: All elderly patients who are hospitalized with or without multiple comorbidities with an acute form of stressors must be evaluated aggressively for precipitants and adequately treated to prevent myocardial injury.